A structure based model for liposome disruption and the role of catalytic activity in myotoxic phospholipase A(2)S - Murakami, M. T.; Arni, R. K. (Elsevier B.V., 2003)
Venom phospholipase A(2)s (PLA(2)s) display a wide spectrum of pharmacological activities and, based on the wealth of biochemical and structural data currently available for PLA(2)S, mechanistic models can now be inferred to account for some of these activities. A structural model is presented for the role played by the distribution of surface electrostatic potential in the ability of myotoxic D49/K49 PLA(2)s to disrupt multilamellar vesicles containing negatively charged natural and non-hydrolyzable phospholipids. Structural evidence is provided for the ability of K49 PLA(2)s to bind phospholipid analogues and for the existence of catalytic activity in K49 PLA(2)s. The importance of the existence of catalytic activity of D49 and K49 PLA(2)s in myotoxicity is presented. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: phospholipase A(2); Lys49 PLA(2); Asp49 PLA(2); liposomes; surface electrostatic potential; catalytic activity